2019
DOI: 10.1155/2019/5825067
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Chair-Side Dental Fear Treatment: Long-Term Follow-Up in Public Health Setting

Abstract: Aim. Purpose of this practice and data-based study was to evaluate the outcome of dental fear treatment of patients referred to the Clinic for Fearful Dental Patients (CFDP) in the primary oral health care, City of Oulu, Finland, during period 2000–2005. Methods. A psychological approach including behavioral interventions and cognitive behavioral therapy (BT/CBT) was used for all participants combined with conscious sedation or dental general anesthesia (DGA), if needed. The outcome was considered successful i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Of note, another open issue involves the investigation of sedation procedures separately from psychological and behavioral evaluations. A previous study showed a long-term reduction of dental fear in children thanks to behavioral and cognitive-behavioral interventions, while conscious sedation was less effective [31]. Furthermore, there was no strong evidence of anxiolytic effects of specific drugs such as opioids, which can lead to difficult social management if overprescribed.…”
Section: Discussionmentioning
confidence: 92%
“…Of note, another open issue involves the investigation of sedation procedures separately from psychological and behavioral evaluations. A previous study showed a long-term reduction of dental fear in children thanks to behavioral and cognitive-behavioral interventions, while conscious sedation was less effective [31]. Furthermore, there was no strong evidence of anxiolytic effects of specific drugs such as opioids, which can lead to difficult social management if overprescribed.…”
Section: Discussionmentioning
confidence: 92%
“…The aim of this retrospective, data-based 10-year follow-up study was to assess the effect of dental fear treatment in the Clinic for Fearful Dental Patients (CFDP) in the City of Oulu, Finland, on dental attendance in primary health care as indicated by examinations, emergency visits and missed appointments. During the 10-year-follow-up, those who had been referred to dental fear treatment at an early age (< 10 years) or whose dental fear treatment was considered successful in 2006 [ 20 ] had more dental examinations than the rest. As for emergency visits and missed appointments, no association with the success of dental fear treatment was discovered.…”
Section: Discussionmentioning
confidence: 99%
“…The present study population was 152 patients who made up 93% of the population evaluated in 2006 for the success of dental fear treatment with a follow-up period of about 2 years. Most participants were children living at home at the time of the original dental fear treatment (2000–2006) and still lived in Oulu in 2016 (93%) [ 20 ]. Because the lack of nationwide welfare databases before year 2017 records of those patients`who have moved to another area or continued their dental care in private dental offices were missing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, patients with dental anxiety have special needs that require both a dental professional and a psychological therapist. The dental fear cycle was well-studied by David Locker, and behavioral and cognitive therapies (BCT) are indicated to treat dental anxiety [ 48 ]. During BCT, patients need to be exposed to dental care progressively, in a positive situation without pain exposition nor negative judgment.…”
Section: Discussionmentioning
confidence: 99%